Development potential of extracellular matrix hydrogels as hemostatic materials - Cai, Dan; Weng, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
The entry of subcutaneous extracellular matrix proteins into the circulation is a key step in hemostasis initiation after vascular injury. However, in cases of severe trauma, extracellular matrix proteins are unable to cover the wound, making it difficult to effectively initiate hemostasis and resulting in a series of bleeding events. Acellular-treated extracellular matrix (ECM) hydrogels are widely used in regenerative medicine and can effectively promote tissue repair due to their high mimic nature and excellent biocompatibility. ECM hydrogels contain high concentrations of extracellular matrix proteins, including collagen, fibronectin, and laminin, which can simulate subcutaneous extracellular matrix components and participate in the hemostatic process. Therefore, it has unique advantages as a hemostatic material. This paper first reviewed the preparation, composition and structure of extracellular hydrogels, as well as their biocompatibility and safety, and then analyzed the hemostatic mechanism of the hydrogels to provide a reference for the application and research, and development of extracellular matrix hydrogels in the field of hemostasis.